Adaptive Envelopes Systems and Mechanisms and their Impact on Building Efficiency - ونوس, سماهر; بدر, رنا; حمزة, نغم (Latakia University Journal -Engineering Sciences Series, 2021)
During current context of insecurity in energy supply and the search for solutions to improve the environmental and energy performance in buildings, especially in envelopes which intermediary between internal and external environment, responsible for the exchange of energy and environmental elements, under technological development, adaptive envelopes idea arose that modifies external environment effect on buildings, thus improving its internal environment in way that saves energy and achieves the greatest possible efficiency in use of materials. Smart materials have been used to design these envelopes, and it became necessary to have sufficient knowledge about properties and physical behavior of these materials, which resulted adaptation mechanisms, which Through it these envelopes become able to respond to changes in external environment dynamically, using Kinetic systems (depends on changes in physical shape of smart materials) and static systems (depends on properties of smart materials). Hence, the research problem emerged Can the impact of the type of system and adaptation mechanism used in adaptive envelope on building efficiency be determined? therefore determine the optimal system and mechanism in achieving each efficiency? The objective of research is to study the impact of various systems and adaptation mechanisms used in adaptive envelopes on buildings efficiency and compare them to determine the optimal system and mechanism in achieving each efficiency. In order to achieve the desired objectives, models of systems and mechanisms used in adaptive envelopes for some examples have been studied and compared in terms of the impact of system and mechanism type used in each of them on environmental, energy and aesthetic efficiency, the optimal system and mechanism in achieving each efficiency have been reached.